2016
DOI: 10.1002/admi.201500738
|View full text |Cite
|
Sign up to set email alerts
|

Highly Hydrophobic and Chemically Rectifiable Surface‐Anchored Metal‐Organic Framework Thin‐Film Devices

Abstract: (MOFs) in common organic solvents which heavily limits thin-film processing on various support substrates for fabrication of devices. SURMOFs are in principle possible to achieve virtually on any support including flexible plastic and cloth substrates with molecular-level control of the dimensionality as well as functionality. [2] Subsequent loading of guest molecules opens-up an immense opportunity of SURMOFs for applications in storage and separation of gas and liquid, making highly specific sensors, perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 51 publications
(46 reference statements)
4
48
0
Order By: Relevance
“…2a). Apart from the distinctive chemical identity, a notable difference between the surface morphological features of pristine and doped Cu-BTEC thin lms is the presence of a reasonably higher number of air-pockets in the latter compared to the former system that could generate highly hydrophobic surfaces 32 as was observed in respective zoomed-in FE-SEM images (Fig. S1 †).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…2a). Apart from the distinctive chemical identity, a notable difference between the surface morphological features of pristine and doped Cu-BTEC thin lms is the presence of a reasonably higher number of air-pockets in the latter compared to the former system that could generate highly hydrophobic surfaces 32 as was observed in respective zoomed-in FE-SEM images (Fig. S1 †).…”
Section: Resultsmentioning
confidence: 90%
“…S16 †). 32,53 The Raman band of pristine Cu-TCNQ at 520 cm À1 (perhaps due to the Cu/Cu interaction mode) was absent in our doped thin lm (Fig. S17 †).…”
Section: Resultsmentioning
confidence: 93%
“…The rise of electrically conductive metal–organic frameworks (MOFs) has positioned these coordination frameworks, traditionally considered insulating, as promising alternatives to classical conductive materials for the development of electronic devices . The combination of high crystallinity, chemical versatility, and porosity with electrical conductivity makes them appealing candidates for energy storage platforms, field‐effect transistors (FETs), Schottky barrier diodes, thermoelectrics, resistive random‐access memories, rectifiers, or ion‐to‐electron transducers . Besides the search for new materials, research efforts have centered in gaining chemical control over their design to optimize the electrical conductivity.…”
Section: Figurementioning
confidence: 99%
“…A recent study has shown that mixing MeCN with H 2 O has significant influence over the thermodynamic (vapor pressure, softness parameter, excess molar Gibbs energy, and enthalpy of mixing), surface tension, viscosity, polarity, and acidity/basicity properties of the resultant mixture . In addition, the aprotic/protic solvent mixture would also lead to a significant change in the dielectric environment . In our case, we believe that when water is added to MeCN, the changes in these properties of the reaction medium slows down the reaction kinetics, which in turn plays an important role in modulating the kinetics of CuTCNQ crystallization and dissolution.…”
Section: Resultsmentioning
confidence: 62%